New realization method for calculating convective heat transfer near the hypersonic aircraft surface - Ryzhkov, Sergei V.; Kuzenov, Victor V. (Zeitschrift für angewandte Mathematik und Physik, 2019)
The feasibility of a realization method for the three-dimensional surface of an aircraft moving with hypersonic velocity is numerically investigated. An approximate mathematical method, which has the same accuracy at much lower computational cost, is used for calculating convective heat transfer over complex geometric shape of a vehicle. Unstructured grids are applied for numerical tests. The hypersonic aircraft computational aerodynamic predictions and comparisons with experimental data are performed.